MAKNA ASTANGGA YOGA PATANJALI - I Ketut Madja (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Basic dconept of yoga teaching lies on the body books of Hindu, they are Veda and Upanisad, and then on its progress, the conept of yoga is provided with some expression by Maha Rsi Patañjali in his book of yoga. This concept is well known with Astangga Yoga, written with eight stages called Astangga Yoga, and are regarded to be a system, are such as composed and woven together with, so that from beginning of the stages until the last is called Samadhi, have the integrative relation, and can not be sparated one each other. From the beginning stage until the last stage has each its use. This of course for those who want to practice them all seriously, will get the good health. The conclusion is that the use of stages of Astangga Yoga are; to develope healt, and the union with The Creator (God)